Combinations of normal and non-normal modal logics for modeling collective trust in normative MAS - Smith, Clara Patricia; Ambrossio, Agustín; Mendoza, Leandro; Rotolo, Antonino (2012)
We provide technical details for combining normal and a non-normal logics for the notion of collective trust. Such combinations lead to different levels of expressiveness of the system. We give a possible structure for a combined model checker for one of the logic resulting from such combinations.
Formato de archivo: PDF. -- Este documento es producción intelectual de la Facultad de Informática - UNLP (Colección BIPA/Biblioteca)
International Workshop AICOL-III, Held as Part of the 25th IVR Congress. (25ª:2011, Ago. 15-16:Frankfurt, Alemania), Berlin:Springer; 2012 (Lecture Notes in Computer Science; 7639), pp. 189-203.
Keywords: MODELOS